Self-synchronization Voltage Source LVRT Control Method for New Energy Inverter under Weak Grid - Dan LIU; Kezheng JIANG; Yiqun KANG; Xiaotong JI; Yunyu XU; Fang LIU (Zhongguo dianli)
The self-synchronization voltage source control technology of the grid-connected inverter is of great significance to the construction of new power system dominated by renewable energy. When the voltage of weak grid drops, the traditional self-synchronization control strategy will have a series of problems in the process of low voltage ride through (LVRT), such as the large transient current impact, the instability of weak grid voltage, and the imbalance of voltage-current control ability, which are caused by the large grid impedance and phase angle difference. For this reason, the relationship between the grid voltage vector and the grid impedance and the grid-connected current in the case of voltage sag under the weak grid, as well as the influencing factors are derived in this paper. Furthermore, a multi-state following self-synchronization voltage source LVRT control method based on stable and transient impedance reshaping is proposed to balance the control ability between voltage and current through steady-state impedance, and ensure the transient control and smooth transition of voltage and current in the whole process through transient impedance reshaping. At the same time, a transient control strategy based on multi-state following is proposed to further ensure the smooth switching and stable operation during the voltage drop and recovery process under weak grid, which can firstly deliver reactive power to support the grid voltage, and compensate the impact of transient overvoltage and overcurrent caused by phase angle and amplitude mutation to help the grid voltage transit smoothly. Finally, the correctness and effectiveness of the proposed control method are verified in MATLAB/Simulink.